Drying methods affect physicochemical and functional characteristics of Clanis Bilineata Tingtauica Mell protein - Wang, Shuya; Niu, Liqiong; Zhou, Bin; Peng, Yao; Yang, Xinquan; Shen, Yingbin; Li, Shugang (Frontiers in Nutrition, 2022)
Abstract: Clanis Bilineata Tingtauica Mell Protein (CBTMP) was a kind of natural full-price protein which has a bright application prospect in the food industry. Since the functional properties of protein can be significantly affected by drying method, this study aims to explore the effect of different drying methods, namely freeze drying (FD), vacuum drying (VD) and hot-air drying (HD) on the structure and functional properties of CBTMP. The results showed that the degree of oxidation of CBTMP was found to be in the following order: HD>VD>FD. Functional characteristics revealed that the CBTMP prepared by VD had the best foaming (150.24±5.34 ℃). However, FD exhibited the best stability of emulsion and rheological properties. Differential scanning calorimeter (DSC) showed CBTMP made by HD had the best thermal stability (Tp=91.49±0.19 ℃), followed by VD (Tp=90.78±0.21 ℃) and FD (Tp=77.53±0.19 ℃). Digestive properties reflected that heating treatment could significantly increase its degree of hydrolysis. To sum up, the research could provide experimental guidance and theoretical support for the preparation method and utilization of CBTMP.